Persepsi Masyarakat Terhadap Keberadaan Taman Nasional Gandang Dewata (Studi Kasus Desa Sikamase Kecamatan Bambang Kabupaten Mamasa) - Utami A, Widyanti; Sarif, Muhammad; Manaf, Abdi (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2024)
National parks serve as excellent conservation sites to observe the splendor of natural events, particularly for viewing unique, endangered, and protected plant and animal species. This research aims to understand how the local people perceive the presence of Gandang Dewata National Park (TNGD) in Sikamase Village. The study employs a detailed interview technique combined with a qualitative descriptive method. Findings from this research indicate that the perception of Gandang Dewata National Park among the local population in Sikamase Village is that it can stimulate economic growth for the surrounding community. The management, specifically BBKSDA Makassar, frequently engages with the local residents, particularly those in the surrounding villages, to promote awareness. Collaborative efforts between the community and park management are undertaken to ensure the ongoing protection of TNGD. The communication established by BBKSDA Makassar extends from management practices to community empowerment initiatives in the buffer areas of TNGD. The security in the TNGD region is notably effective, primarily due to regular patrols conducted by management groups, including the forestry police and the Polhut Partner Community (MMP), which significantly reduces the likelihood of encroachments in the area. The establishment of TNGD in Mamasa Regency is viewed positively by the locals, demonstrated by their support for management efforts and active participation in roles such as Polhut Partner Communities (MMP), Fire Care Communities (MPA), and Village Facilitators (Fasdes) aimed at fostering sustainably managed conservation zones. Although management has extensively communicated with local government and the community, disagreements still persist on issues like illegal hunting, the collection of forest resources without proper authorization, and land encroachments.